Surgical treatment of advanced medication-related osteonecrosis of the jaws: Comparison of soft tissue closure techniques and evaluation of side effects. Issue 9 (September 2020) - Ahrenbog, Greta; Gottsauner, Maximilian; Meier, Johannes K.; Ettl, Tobias; Reichert, Torsten E.; Klingelhöffer, Christoph
Abstract: The aim of the study was to evaluate the surgical outcome of patients with advanced medication-related osteonecrosis of the jaw (MRONJ) treated with different flaps for soft tissue closure. Only MRONJ stage III patients with a minimum follow-up of 6 months were included in our prospective study. The soft tissue closure techniques were: Mylohyoid Muscle Flap, Buccal Fat Flap and mucoperiosteal flap alone. Potential risk factors and surgical side effects were analyzed. Relapses occurred in 12 of 44 included cases and 38 reached mucosal integrity within the follow-up. Cases treated with the muscle or fat flap showed better results regarding the recurrence rate (p < 0.001) and soft tissue healing (p = 0.002): only 3 of 33 developed a relapse, and 31 of 33 reached mucosal integrity. The outcome was worse if MRONJ occurred at the front areas of the jaw (p = 0.025). Postoperative, the pain level was reduced significantly (p < 0.001). Partial hypoesthesia of the lip arose in 18 cases. An impairment of the long-term prosthetic rehabilitation has not been seen.Patients with MRONJ stage III undergoing surgery benefit from extensive soft tissue closure. Highlights: Local flaps for wound closure lead to a significantly lower recurrence rate. The chance of sufficient mucosal closure was higher if a local flap was used. A surgical treatment leads to a significant reduction of pain and halitosis. A partial hypoesthesia of the lip was a frequent side effect. The long-term prosthetic rehabilitation has not been degraded by surgery.